Orange Juice Attenuates Circulating miR-150-5p, miR-25-3p, and miR-451a in Healthy Smokers: A Randomized Crossover Study - Dorna, Mariana S.; Barbosa, Elizabete M. S.; Callegari, Matheus A.; Tanni, Suzana E.; Chiuso-Minicucci, Fernanda; Felix, Tainara F.; Seneda, Ana L.; Correa, Camila R.; Fernandes, Ana A. H.; Azevedo, Paula S.; Polegato, Bertha F.; Rogero, Marcelo M.; et al. (Frontiers in Nutrition, 2021)
Introduction: Tobacco smoke is associated with oxidative and inflammatory pathways, increasing the risk of chronic-degenerative diseases. Our goal was to evaluate the effects of acute “Pera” and “Moro” orange juice consumption on inflammatory processes and oxidative stress in microRNA (miRNA) expression in plasma from healthy smokers. Methods: This was a randomized crossover study that included healthy smokers over 18 years old. Blood samples were collected before and 11 hours after beverage ingestion. Participants were instructed to drink 400 mL of Pera orange juice (Citrus sinensis), Moro orange juice (Citrus sinensis L. Osbeck), or water. Each subject drank the beverages in a 3-way crossover study design. Inflammatory and oxidative stress biomarkers and circulating miRNA expression profiles were determined. The subjects maintained their usual tobacco exposure during the experiment. Results: We included 18 individuals (12 men and 6 women), with 37.0 ± 12.0 years old. All subjects received the 3 interventions. Increased expression of circulating miRNAs (miR-150-5p, miR-25-3p, and miR-451a) was verified after cigarette smoking, which were attenuated after intake of both types of orange juice. There was no difference regarding serum levels of TNF-, IL-6, MMP-9, and C-reactive protein. Despite the increased activity of serum superoxide dismutase and glutathione peroxidase after “Pera” or “Moro” orange juice intake, respectively, no changes in lipid hydroperoxide levels were detected. Conclusion: Tobaccos smokers showed increased expression of miR-150-5p, miR-25-3p, and miR-451a was noted, and attenuated by orange juice intake. miRNAs were predicted to regulate 244 target genes with roles in oxidative stress, PI3K-Akt, and MAPK signaling, which are pathways frequently involved in smoking-related cardiovascular diseases and cancer.